(untitled) (The Strategic Review for Southern Africa, 2020)
The startlingly definitive election victory for Zimbabwe’s Zimbabwe African National Union – Patriotic Front (ZANU-PF) at the end of July 2013 incorporated elements ranging from coercion, cheating, and regional connivance (with opposition’s hapless performance) so seamlessly that many scholars and political practitioners have prophesised the near death of democracy there and elsewhere on the continent. This article reviews the process of and the discourse on the election. Historical reflections based on recent archival research offer comparative perspectives. Democratic progress in Zimbabwe must be reassessed soberly and without illusions.